Pemberdayaan Siswa/i Akan Kepedulian Lingkungan Melalui Pemilahan Sampah Menggunakan Tong Sampah Pintar - Fivta Omega Lam Rumata Sinaga; Moria Ester Adelina Br. Butar-Butar; Ica Yolanda Ginting; T.M.P Gold Dian Frans Siagian; Erikson Kennedy Manullang; Winanda Wahana Warga Dalam (Pusat P2M Politeknik Negeri Batam, 2019)
This community service activity aims to improve awareness towards the environment from children on the students in the School of Kusuma Bangsa through the implementation of educational waste sorting and training in the processing of waste. The purpose of carrying out this activities to reduce this problem, namely: 1) Provide education in the sorting and processing of garbage 2) Provide skills in managing waste into innovative products and economic value, 3) Provide training in additional skills such as planting, 4) The target of this activity is the students in the School of Kusuma Bangsa. The method of implementation of these training activities will be made by the method of pre and post test. The output of this activity are: 1) Create the character of students who cares about the environment and is smart in making decisions, 2) Create an innovative products and have the economic value of the problem of found in the School of Kusuma bangsa, 3) Development of skills for students to carry out the third tri darma of higher education, namely community service.